The Effect of Financial Literacy, Lifestyle, and Self-Control on the Consumptive Behavior of Students - Azmi, M. Imron; Utomo, Danang Prio; Ali, Muhammad (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
This study aims to determine the Influence of financial literacy, lifestyle, and self-control affect the consumptive behavior of students. The research method used is quantitative through the type of correlation research. The use of this research sample is students of the Faculty of Social Sciences and Economics with a total of 93 students. The research technique used Propotional Random Sampling and Accidental Sampling with data collection in this study by distributing questionnaires.  Based on the results of data analysis, partially there is a positive     influence on financial literacy variables with a t value> t table (2.187> 1.990), lifestyle variables with a t value> t table (7.047> 1.990), self-control variables with a t value> t table (2.772> 1.990). So that through simultaneous good impact between financial literacy variables, lifestyle, and self-control on consumptive behavior. This is evidenced by the value of F count> F table (19.951> 2.70) with a significant 5%. It can be concluded that partially or simultaneously the variables of financial literacy, lifestyle, and self-control have a positive effect on consumptive behavior. The results of the coefficient of determination test on variables X1, X2, and X3 are 0.382, this means that consumptive behavior is influenced by the variables of financial literacy (X1), lifestyle (X2), and self-control (X3) by 38.2% while the remaining 61.8% is influenced by other variables.